Former Yugoslav Republic of Macedonia : Selected Issues. (IMF Staff Country Reports; Country Report, 2009)
This Selected Issues paper for the former Yugoslav Republic of Macedonia is examined. Real GDP growth accelerated to 5 percent in 2007 and 6 percent in the first half of 2008, from its historical average of about 3 percent. Increased investment, partly financed by FDI, is the main driver boosting domestic demand, as seen in the fast-growing import of investment and intermediate goods. Simultaneously, the current account deficit has widened substantially since 2007 and has become a major concern for macroeconomic stability.